Correlating Boron–Hydrogen Stretching Frequencies with Boron–Hydrogen Bond Lengths in Closoboranes: An Approach Using DFT Calculations. Issue 2 (22nd January 2018) - Hagemann, Hans; Sharma, Manish; Sethio, Daniel; Lawson Daku, Latévi Max
Abstract : Using harmonic and anharmonic DFT calculations, we have established a general correlation between B–H stretching frequencies and B–H bond lengths valid for the closoboranes B x H x 2 − ( x = 6 – 12), substituted closoboranes B12 H12 – n X n 2 − (with X = F, Cl, Br and n = 1 – 3 and 9 – 12) and the carboranes CB 9 H 10 − and CB 11 H 12 −, suggesting that this correlation is also applicable to other similar species. It appears that the average B–H stretching frequency observed around 2500 cm −1 shift by about −100 cm −1 if the average B–H bond length increases by 1 pm. In contrast to BH 4 −, the B–H bond in closoboranes is practically covalent and the correlation evidenced between its stretching frequency and its length proves to be similar to the one observed for the C–H bond. Abstract :